Assessing GIFT adoption potential among aquaculture farmers in Nasarawa and Kwara States, Nigeria - Manyise, Timothy; Lozano, Denise; Olaniyi, Ajibola; Siriwardena, Sunil; Rossignoli, Cristiano (WorldFish, 2024)
This study examines the adoption potential of Genetically Improved Farmed Tilapia (GIFT) among grow-out fish farmers and hatchery operators in selected regions of Nigeria. Despite the proven benefits of GIFT, including faster growth rates, disease tolerance, and high yield, a knowledge gap exists among farmers regarding the strain. Initially, a few farmers were aware of GIFT, but after receiving brief introductions, the majority expressed interest in adopting it. Key factors influencing interest include faster growth rates, disease tolerance, high yield, and market preference. Based on these findings, several recommendations are proposed to enhance GIFT adoption. Increasing awareness through targeted education campaigns using workshops, extension services, and accessible media platforms is essential. Providing hands on training on GIFT production and management practices will help bridge the knowledge gap and build confidence. Facilitating access to quality GIFT fingerlings and broodstock through public-private collaboration will support farmers in their adoption efforts. Emphasizing the economic benefits of GIFT adoption through success stories and case studies can motivate others. Continuous technical support and extension services should be offered to optimize farming practices, and strengthening farmer associations will create supportive networks for knowledge exchange and resource access. By implementing these recommendations, GIFT adoption can be accelerated, fostering sustainable aquaculture practices and enhancing the livelihoods of small-scale farmers in Nigeria.